E-DOCUMENT SYSTEMS: TRENDS AND PERSPECTIVES - Iskakova А.К.; Berkimbaeva С.Б.; Akkoziyeva Р.С.; Yeleussinova А.У. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The rapid growth of information flows in science, business, production, education, culture requires appropriate adequate from modern IT technologies. for 21st century society is onerous spending a huge amount of paper, and information coming on such media, less than electronic. Electronic document systems (SED) are taking on increasing activity in modern conditions and are being introduced both to automate document flow management and as a platform for a single information system that expands the boundaries of capabilities and, accordingly, attracts the attention of the scientific and management communities. With the timely development of the country’s economy, in general, and business companies create new problems associated with the management, processing, storage and control of the increasing volume of data flows. The article aims to consider the prospects and trends in the development of electronic document systems (SED), in the preconditions for the creation and briefly describes the history of the formation of the SED.